Efforts To Improve the Competencies of The Alpha Generation Through a Project-Based Learning Model in Class 3 Science Lessons at MI Al Fithrah Surabaya - Choirun Nisa; Ficky Dewi Ixfina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research aims to improve the competence of Generation Alpha through the implementation of Project Based Learning (PjBL) model in Natural and Social Sciences (IPAS) subjects for 3rd grade students at MI Al Fithrah Surabaya. Generation Alpha, born between 2010-2024, has unique learning characteristics, including being accustomed to digital technology, visual-oriented, and requiring interactive and contextual learning. The research method used was Classroom Action Research (CAR) with two cycles. The research subjects were 28 third-grade students at MI Al Fithrah Surabaya. Instruments used included competency tests, learning activity observations, student response questionnaires, and project portfolio documentation. The results showed a significant improvement in student competence. In the first cycle, the average competency score reached 72.5 with classical mastery of 68%. After improvements in the second cycle, the average score increased to 85.3 with classical mastery of 93%. The implementation of PjBL was able to improve students' cognitive, affective, and psychomotor competencies. Additionally, this model also enhanced learning motivation, creativity, and collaboration skills. This research recommends the implementation of PjBL as an effective learning model to accommodate the learning needs of Generation Alpha in IPAS subjects at elementary schools.